Choice of Surgical Tactics for Calculus Anuria in Young Children - A.A. Nasirov; Kh.N. Khotamov; F.F. Bayakhmedov (Western European Studies, 2024)
Selection of surgical treatment tactics depending on the duration and complications of calculus anuria in young children
Keywords: anuria; surgical treatment of children